Proceedings of Seminar on Rural Industrialisation - Planning Commission (Planning Commission, 1984)
The scenario obtainable for the developing economy of India is that about 76 per cent of the people live in rural areas and more than two-third of the work-force is engaged in agriculture activities and that most of these pursuits provide only subsidiary level existence. The Indian villages, which number about 5.5 lakhs, are spread too widely and most of them are still not well connected with each other or with urban centres through all weather roads or through waterways and railways. What this indicates (in comparison to the economic structure of the developed economies) is that there is excessive pressure of population on agriculture which would need to be shifted to other avocations in the secondary and tertiary sectors.
Government of India Planning Commission
Government of India Planning Commission